2004
DOI: 10.4049/jimmunol.173.2.1051
|View full text |Cite
|
Sign up to set email alerts
|

Requirements of NK Cells and Proinflammatory Cytokines in T Cell-Dependent Neonatal Autoimmune Ovarian Disease Triggered by Immune Complex

Abstract: A model of neonatal autoimmune disease has been described recently in which an epitope-specific autoantibody to murine zona pellucida 3 induces severe ovarian disease in neonatal, but not adult, mice (neonatal AOD). The autoantibody forms immune complex with endogenous ovarian zona pellucida 3, and a pathogenic CD4+ T cell response is triggered. The basis for the predominant neonatal susceptibility has not been clarified. In this study innate immunity, including neonatal NK cells, in neonatal AOD was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
(34 reference statements)
2
27
0
Order By: Relevance
“…However, whether NK cells promote or protect against autoimmunity remains unclear with evidence from cell depletion studies suggesting that NK cells play a role in both promoting and limiting autoimmunity in different disease models and different stages of autoimmune responses. A protective role for NK cells has been reported in animal models of diabetes [60], colitis [61] and experimental autoimmune encephalomyelitis [62,63], while in contrast, NK cells have been shown to promote autoimmunity in models of neonatal autoimmune ovarian disease [64] and experimental autoimmune myasthenia gravis [65]. Recent reports have also outlined conflicting results on the effect of NK cell depletion in animal models of arthritis [66,67].…”
Section: Nk Cells In Autoimmune Diseasesmentioning
confidence: 95%
“…However, whether NK cells promote or protect against autoimmunity remains unclear with evidence from cell depletion studies suggesting that NK cells play a role in both promoting and limiting autoimmunity in different disease models and different stages of autoimmune responses. A protective role for NK cells has been reported in animal models of diabetes [60], colitis [61] and experimental autoimmune encephalomyelitis [62,63], while in contrast, NK cells have been shown to promote autoimmunity in models of neonatal autoimmune ovarian disease [64] and experimental autoimmune myasthenia gravis [65]. Recent reports have also outlined conflicting results on the effect of NK cell depletion in animal models of arthritis [66,67].…”
Section: Nk Cells In Autoimmune Diseasesmentioning
confidence: 95%
“…Recent studies of both autoimmune disease (52) and allogeneic IUHCT (53) rism (<1.8%) despite the presence of T cell tolerance. Our findings of transfer of maternal alloantibodies would suggest that a possible mechanism for this observation is activation of donor MHC class I-specific NK cells by maternal alloantibody via an ADCC mechanism in a milieu of low frequencies of donor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Complement C3b and C5b were undetectable in ovaries of mice with nAOD. However, studies with blocking antibodies and gene KO mice indicated that nAOD is dependent on FcγRIII expression (44, 58). In fact, we found that TD-nAOD pathogenesis requires both FcγRIII-dependent ADCC and a de novo T cell response.…”
Section: How Do the Maternal Zp3 Autoab Cause Ovarian Injury?mentioning
confidence: 99%
“…In fact, we found that TD-nAOD pathogenesis requires both FcγRIII-dependent ADCC and a de novo T cell response. First, the neonatal NK cell must express FcγRIII to support nAOD (58). Second, the critical CD4 + T cells are required in TD-nAOD because (1) T cell depletion prevents nAOD, (2) CD4 + T cells from mice with nAOD transfer ovarian disease to naïve pups (44).…”
Section: How Do the Maternal Zp3 Autoab Cause Ovarian Injury?mentioning
confidence: 99%